2002
DOI: 10.1046/j.1365-2311.2002.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Bt‐toxin by herbivores feeding on transgenic maize and consequences for the predator Chrysoperla carnea

Abstract: Abstract. 1. Chrysoperla carnea is an important predatory insect in maize. To assess the ecological effects of Bt-maize, expressing the Cry1Ab protein, on larvae of this predator, the following factors were examined: (1) the performance of three prey herbivores (Rhopalosiphum padi, Tetranychus urticae, and Spodoptera littoralis) on transgenic Bt and non-transgenic maize plants; (2) the intake of the Cry1Ab toxin by the three herbivores; and (3) the effects on C. carnea when fed each of the prey species.2. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
292
1
15

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(332 citation statements)
references
References 17 publications
24
292
1
15
Order By: Relevance
“…In one study, the aphid Rhopalosiphum maidis (Fitch) (Hemiptera: Aphididae) was found to perform considerably better on six Bt maize lines expressing Cry1Ab than on the near isogenic respective lines, resulting in exceptionally higher numbers on these Bt plants (Faria et al 2007). Other studies, however, showed that there were no effects of Bt maize on aphids (Head et al 2001, Raps et al 2001, Bourguet et al 2002, Dutton et al 2002. Similarly, performance by thrips, F. tenuicornis (Uzel) and Anaphothrips obscurus (Muller) (Thysanoptera: Thripidae), in their study was not signiÞcantly different between Bt and non-Bt maize in studies by Zwahlen et al (2000), Obrist et al (2005), but thrips density was signiÞcantly higher in Bt maize in the study of Bourguet et al (2002).…”
Section: Discussionmentioning
confidence: 79%
“…In one study, the aphid Rhopalosiphum maidis (Fitch) (Hemiptera: Aphididae) was found to perform considerably better on six Bt maize lines expressing Cry1Ab than on the near isogenic respective lines, resulting in exceptionally higher numbers on these Bt plants (Faria et al 2007). Other studies, however, showed that there were no effects of Bt maize on aphids (Head et al 2001, Raps et al 2001, Bourguet et al 2002, Dutton et al 2002. Similarly, performance by thrips, F. tenuicornis (Uzel) and Anaphothrips obscurus (Muller) (Thysanoptera: Thripidae), in their study was not signiÞcantly different between Bt and non-Bt maize in studies by Zwahlen et al (2000), Obrist et al (2005), but thrips density was signiÞcantly higher in Bt maize in the study of Bourguet et al (2002).…”
Section: Discussionmentioning
confidence: 79%
“…O material congelado foi pesado e misturados à solução PBST 1:10 (peso/volume), sendo essa concentração utilizada para as folhas de algodoeiro. Dada a alta concentração da toxina esperada a ser quantifi cada no ácaro rajado (Dutton et al 2002, Torres et al 2006, nesse caso empregou-se diluição 1:40 (peso/volume) para a extração da toxina. O produto sobrenadante foi centrifugado a 4000 rpm por um minuto em centrífuga 80-2B Centribio, com rotor de ângulo fi xo (45º) e raio de 7 cm.…”
Section: Biologia De P Macropilisunclassified
“…Essas toxinas são produzidas constitutivamente pela planta, mas predominantemente nas folhas. Ao serem expressas continuamente, as toxinas fi cam expostas aos demais herbívoros não-alvos e, consequentemente, aos seus inimigos naturais (Dutton et al 2002, Obrist et al 2006a, Torres et al 2006, Torres & Ruberson 2008. Entretanto, nenhum dos trabalhos realizados até o momento avaliaram os possíveis efeitos subletais das toxinas Cry ao longo de gerações ou indiretos, através da planta e comportamentais, na biologia e comportamento de T. urticae, praga não-alvo do algodoeiro Bt, mas que apresenta considerável exposição à toxina.…”
unclassified
“…In particular, the green lacewing (Chrysoperla carnea), an important predator in many maize growing areas, has thoroughly been studied since studies suggested that this predator was negatively affected by Cry1Ab [31][32][33]. Results of subsequent studies using several different prey species reared on Cry1Ab-maize, however, showed that the insecticidal protein itself does not directly affect this predator, but that the green lacewing may be affected when feeding on prey species that are susceptible to Bttoxin [34][35][36]. The negative effect observed was thus entirely prey-quality mediated, i.e., caused by the suboptimal food quality of the lepidopteran larvae used in the experiments.…”
Section: Lower-tier Studies In the Laboratory And Greenhousementioning
confidence: 99%